Diagnosis of dysplasia in upper gastro-intestinal tract biopsies through digital microscopy - Dorina Gui; Galen Cortina; Bita Naini; Steve Hart; Garrett Gerney; David Dawson; Sarah Dry (Elsevier, 2012)
Background: Whole slide digital imaging (WSDI) offers an alternative to glass slides for diagnostic interpretation. While prior work has concentrated on the use of whole slide digital imaging for routine diagnostic cases, this study focuses on diagnostic interpretation of digital images for a highly challenging area, upper gastro-intestinal (GI) dysplasia. The aim of this study is to study the accuracy and efficiency of WSDI in the diagnosis of upper GI tract dysplasia. Materials and Methods: Forty-two hematoxylin and eosin (H and E)-stained slides representing negative, indefinite, low grade and high grade dysplasia were selected and scanned at 20x (Aperio XT). Four attending GI pathologists reviewed the WSDI, then glass slides, with at least 3-4 weeks between each media; glass slides were re-reviewed 16-18 months later. Results: Intraobserver variability for three clinically relevant categories (negative, indefinite/low grade, high grade) was wider for WSDI to glass (kappa range 0.36-0.78) than glass to glass (kappa range 0.58-0.75). In comparison to glass slide review, WSDI review required more time and was associated with an unexpected trend toward downgrading dysplasia. Conclusions: Our results suggest: (1) upper GI dysplasia can be diagnosed using WSDI with similar intraobserver reproducibility as for glass slides; however, this is not true for all pathologists; (2) pathologists may have a tendency to downgrade dysplasia in digital images; and (3) pathologists who use WSDI for interpretation of GI dysplasia cases may benefit from regular, on-going, re-review of paired digital and glass images to ensure the most accurate utilization of digital technology, at least in the early stages of implementation.